CEO characteristics, firm reputation and firm performance after merger and acquisition - Edi; Yuswar Z. Basri; Willy Arafah (Verslas: Teorija ir praktika / Business: Theory and Practice, 2020)
This study examine the impact of Firm reputation and CEO Characteristics toward firm performance after corporate action acquisition and merger. This study also examines how CEO characteristics mediates firm reputation to maximize firm performance after acquisition. This research objectives are firm that listed in Indonesia stock exchange between 2010 till 2016 and executing corporate action mergers and acquisitions. To select the research sample, this research conducted purposive sampling. This research data analysis are using e-views program to conduct descriptive statistical test, outlier test and hypothesis test. The results of this study show that by choosing an experienced, capable and aggressive CEO can maximize firm reputation and firm performance. We also find that a capable and experienced CEO able to mediates firm reputation as resources for maximize the firm performance. These research findings will be helpful for management in maximize firm performance by using acquisition and merger as business strategy, management can set the standard requirement for firm reputation and choosing a new CEO to take charge in acquisition project as their intangible resources. The novelty of this research are provide a new insight of acquisition as how CEO characteristics effect firm performance by using firm reputation as mediating variable.
Keywords: G11; G31; M14; 650; acquisition; CEO characteristics; firm performance; firm reputation; Indonesia; mergers